Tindak Pidana Penipuan Investasi Fiktif di Pasar Modal Menggunakan Skema Piramida - Ni Putu Rai Santi Pradnyani; I Nyoman Putu Budiartha; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2022)
The rise of investment fraud in Indonesia has been driven by several factors, such as a lack of public awareness of the financial sector, especially legal investments, and the plight of those seeking high returns ignoring risk. The victims of fictitious investment are not only from the lower middle class, but also the educated or upper class with higher education. This research aims to find out how the legal arrangements for investment managers to commit fraud in the capital market using a pyramid scheme, and the criminal sanctions they will receive. This research is normative legal research conducted with a case and legislation approach. As a result, in cases of fraud, two sides can be found, namely the side that is deceived (the victim) and the side that deceives (the perpetrator). Capital Market Law stipulates a regulation whereby parties are required to follow the principle of transparency in trading securities and conducting public offerings on the secondary market. The criminal sanction for fictitious investment managers to commit fraud in the capital market using a pyramid scheme is where the perpetrator performs deviant behavior that meets certain requirements to be subject to criminal sanctions.